Taxing Advocates’ Income in Ethiopia: An In-depth Examination of the Presumptive Tax Assessment Regime - Asegid, Zerihun; Peeters, Bart; Lencho, Taddese (Bahir Dar University Journal of Law, 2024)
This article investigates the presumptive income tax regime for advocates in Ethiopia, focusing on the characterization of advocates’ income as business income, their categorization into Categories A, B, or C taxpayers, and the presumptive income tax assessment of Category C advocates. The study employs a mixed-methods approach, combining doctrinal analysis of legal frameworks with a qualitative examination of tax administration practices. The article finds that Ethiopia’s treatment of advocates under the business income tax schedule is consistent with international norms, simplifying tax administration. However, issues arise with categorization and presumptive tax determination. Despite the principal income tax laws base advocatesâ€Ÿ categorization and presumptive tax assessment on annual turnover, the laws lack clear and objective mechanisms for determining this turnover. Administratively, tax authorities have attempted various turnover estimation methods with limited success due to inappropriate approaches and flawed applications. Non-compliance among advocates further exacerbates these challenges. As a result, categorization and presumptive tax assessments are often subjective, uncertain, and prone to evasion. To address these shortcomings, the article proposes modernizing the presumptive tax regime by introducing effective turnover verification methods, requiring Category C advocates to maintain basic records of receipts with an optional standard deduction for expenses, utilizing robust third-party information frameworks for reliable data exchange, and enhancing tax authorities’ capabilities to implement these reforms. These measures aim to create a more equitable and efficient income tax system for advocates in Ethiopia.